PRACTICAL AND DYNAMIC ACTIVITIES IN SOCIOLOGY CLASSES: PATHWAYS TO CRITICAL AND MEANINGFUL LEARNING - Mazeto, Jhiones de Arruda; de Moraes, Francelina Fontenelle; de Jesus, Camila Aparecida Miranda; Rodrigues, Jozivane Ferreira Silva; Martins, Elkslene Ramos; Martines, Renata Galvani Garcia; Ribeiro, Creuza Rosa; de Lima, Lorrayni Cristina Arruda; Chaves, Rosanilda Meira (Seven Editora, 2026)
This article analyzes the relevance of practical and dynamic activities in the teaching of Sociology in Basic Education, highlighting their role in overcoming excessively theoretical and unattractive traditional methodologies. It starts from the understanding that the teaching of this discipline should enable students to critically read social reality, involving cultural, political, economic, and social aspects. In this context, the use of active methodologies, such as debates, group dynamics, case studies, simulations, and interdisciplinary projects, contributes to making the teaching-learning process more meaningful, participatory, and connected to the students’ daily lives. The study, with a qualitative and bibliographic approach, shows that these practices favor the collective construction of knowledge, stimulate student protagonism, and strengthen skills such as argumentation, communication, and critical reflection. By articulating theory and practice, students are able to understand sociological concepts in a more concrete way, developing greater social and political awareness. In addition, the importance of the teacher’s intentional planning is highlighted, as they act as a mediator in organizing learning experiences that promote student engagement and active participation. In conclusion, practical and dynamic activities are fundamental for promoting meaningful learning, contributing to the formation of critical, conscious individuals capable of acting in the transformation of social reality. Therefore, their use in the teaching of Sociology proves essential for a democratic, contextualized education focused on citizenship.